2002
DOI: 10.1152/ajpregu.00665.2000
|View full text |Cite
|
Sign up to set email alerts
|

Volume expansion during acute angiotensin II receptor (AT1) blockade and NOS inhibition in conscious dogs

Abstract: The responses to AT1-receptor blockade (candesartan 1 mg/kg) and to concomitant volume expansion (saline 35 ml/kg for 90 min) with and without nitric oxide synthase (NOS) ) were investigated in separate experiments in normal dogs. AT1 blockade decreased arterial pressure (106 Ϯ 4 to 96 Ϯ 5 mmHg) and increased glomerular filtration rate (GFR) by 17% and sodium excretion threefold. NOS inhibition increased arterial pressure (103 Ϯ 3 to 116 Ϯ 3 mmHg) and decreased GFR by 21% and reduced sodium excretion by some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…With a combination of NO synthase inhibition and AT 1 blockade, volume expansion induced only a very modest natriuresis. Consistent with these results, infusion of L-arginine as a substrate for NO synthase exaggerates the natriuretic response to volume expansion and counteracts the effect of NO synthase inhibition (2,3,25). These results indicate that NO synthase inhibition abolishes the natriuresis after volume expansion, in part by preventing the suppression of the renin-angiotensin-aldosterone system and show that the NO system plays a dominant role in the hierarchy of control systems that control salt excretion.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…With a combination of NO synthase inhibition and AT 1 blockade, volume expansion induced only a very modest natriuresis. Consistent with these results, infusion of L-arginine as a substrate for NO synthase exaggerates the natriuretic response to volume expansion and counteracts the effect of NO synthase inhibition (2,3,25). These results indicate that NO synthase inhibition abolishes the natriuresis after volume expansion, in part by preventing the suppression of the renin-angiotensin-aldosterone system and show that the NO system plays a dominant role in the hierarchy of control systems that control salt excretion.…”
supporting
confidence: 70%
“…The interplay between the NO system and ANG II in the control of salt excretion during volume expansion in conscious dogs has been investigated in several studies (2,3,25). NO synthase inhibition increased plasma renin and ANG II concentrations and largely abolished natriuresis after volume expansion, whereas acute AT 1 blockade exaggerated the natriuresis.…”
mentioning
confidence: 99%
“…Amlodipine and candesartan cilexetil significantl crease in urine flow, renal sodium, chloride and potassium excretion. [16,17] The present study demonstrate that serum chloride in the amlodipine group was lower than that in the candesartan group and serum sodium at follow up was lower than that at baseline in the candesartan group. However, values of serum sodium and serum chloride were within the normal range.…”
Section: Discussionsupporting
confidence: 47%
“…The observation that NOS substrate donation alone did not change GFR is also compatible with the findings of Salazar's group (1,25,30), who showed repeatedly that blockade of NO synthesis did not induce changes in renal hemodynamics. Several groups including our own, however, reported that NOS inhibition results in a decrease in GFR (3,24,28). Thus the effects of NO on GFR are still unclear.…”
Section: Discussionmentioning
confidence: 85%
“…We previously showed that even modest increases in renal sodium excretion are preceded by and to a large extent regulated by a decrease in the level of activity of the renin system and that an intact NO system is required for this system to be fully operative (2,3). Neither our previous nor our present studies demonstrate definitively whether NO exerts a permissive effect on renal sodium handling, i.e., a certain activity is a necessary prerequisite for regulatory systems to be fully operative, or whether it works as a control system playing in concert with other control systems.…”
Section: Perspectivesmentioning
confidence: 99%